Hubungan Antara Kecerdasan Emosi dan Self Efficacy dalam Pemecahan Masalah Penyesuaian Diri Remaja Awal - Ni Made Wahyu Indrariyani Artha; Supriyadi Supriyadi (Jurnal Psikologi Udayana, 2013)
Adolescence’s life especially the early one cannot be separated from upcoming problems because their physical, cognitive, and socio-emotional changes are significantly affecting their self-controlling and mindset to their surrounding environment. Both of emotion and self-confidence are playing an important role on facing the problems especially on adolescent adjustment. The purposes of this research are to understand the relationship between emotional intelligence and self efficacy in problem solving of adjustment early adolescence and to understand effective contribution of emotional intelligence and self efficacy to problem solving of adjustment early adolescence. The subjects in this research were 129 students of high school in Denpasar especially students in grade 10, who were chosen by simple random sampling. This research used three scales as measurement tools, namely emotional intelligence scale, self efficacy scale, and adjustment scale. Emotional intelligence scale has a reliability value = 0,822, consist of 20 items; self efficacy scale has a reliability value = 0,913, consist of 34 items; and adjustment scale has a reliability value = 0,896, consist of 31 items. According to the result of multiple regression analysis, the value of R correlation = 0,772, F regression = 93,211, p = 0,000, there was relationship between emotional intelligence and self efficacy in problem solving of adjustment early adolescence. The effective contribution of emotional intelligence and self efficacy to adjustment are 59,70%. The result of each correlation emotional intelligence and self efficacy to problem solving of adjustment early adolescence is 0,632 and 0,715; p = 0,000, there was a positive and strength relationship between emotional intelligence and self efficacy in problem solving of adjustment early adolescence. Keywords: emotional intelligence, self efficacy, and problem solving of adjustment